2007
DOI: 10.1091/mbc.e06-09-0840
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Silencing of a Novel hTERT Reporter Locus during In Vitro Differentiation of Mouse Embryonic Stem Cells

Abstract: The human telomerase reverse transcriptase hTERT is highly expressed in undifferentiated embryonic cells and silenced in the majority of somatic cells. To investigate the mechanisms of hTERT silencing, we have developed a novel reporter using a bacterial artificial chromosome (BAC) that contained the entire hTERT gene and its neighboring loci, hCRR9 and hXtrp2. Firefly and Renilla luciferases were used to monitor transcription from the hTERT and hCRR9 promoters, respectively. In mouse embryonic stem cells stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 46 publications
3
59
1
Order By: Relevance
“…For example, strikingly increased risk was found in smoking related cancers, such as lung and bladder cancers. It may be explained that CLPTM1L protein may be involved in the apoptosis response of genotoxic stress [9], [10], [11], [12]. Further more, Nan and collaborators observed a suggestive positive relationship between rs401681 C allele and shorter relative telomere length [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, strikingly increased risk was found in smoking related cancers, such as lung and bladder cancers. It may be explained that CLPTM1L protein may be involved in the apoptosis response of genotoxic stress [9], [10], [11], [12]. Further more, Nan and collaborators observed a suggestive positive relationship between rs401681 C allele and shorter relative telomere length [50].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the coding regions of TERT can affect telomerase activity and telomere length, and generate severe clinical phenotypes, including bone marrow failure syndromes and a substantive increase in cancer frequency [8]. Although the function of the CLPTM1L is largely unknown, studies have demonstrated that it may be involved in the apoptotic response to genotoxic stress induced by cisplatin, as it encodes a transcript whose over-expression has been shown to induce apoptosis in cisplatin-resistant-sensitive cells [9], [10], [11], [12]. Moreover, the CLPTM1L variants are hypothesized to enhance the metabolic activation of the reactive metabolites and/or formation and persistence of DNA adducts [13].…”
Section: Introductionmentioning
confidence: 99%
“…2006; Lee et al . 2006), as well as reduced hTERT expression, at least partly via epigenetic mechanisms (Wang et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
“…To generate reporters for studying transcriptional regulation of the TERT (telomerase reverse transcriptase) genes (16), we inserted luciferase expression cassettes into the initiation codons of the TERT genes in BAC constructs, using the two-step procedure described as follows. To make use of the recombineering method reported by Lee at al.…”
Section: Resultsmentioning
confidence: 99%